IPTEKS PENGARUH MINAT PERILAKU WAJIB PAJAK DALAM MENGGUNAKAN SYSTEM ONLINE DI KPP PRATAMA MANADO - Suci, Tri Sukma M.; Latjandu, Lady D. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Reporting system (SPT) starts the expansion of information technology online & real time, namely e-Filing. With an existence of e-Filing provides convenience to taxpayers in reportin tax returns. The purpose of this study’s to look at the factors that affect interest in taxpayer behavior toward the use of e-Filing at KPP Pratama Manado. E-Filing makes a good contribution to Taxpayers and by using e-Filing, a Taxpayers can feel the benefits, wich one is convenience when delivering taxes. Taxpayers interest in using e-Filing is based on perceptions and the experience gained by taxpayers on e-Filing. Factors of usability, convenience, security and confidentiality, and human resources have a positive influence, so that the benefits of e-Filing can be felt by all Taxpayers registered at the KPP Pratama Manado.Keywords: e-Filing, taxpayers, SPT